Determinan Kepatuhan Wajib Pajak dengan Pengetahuan Sebagai Pemoderasi - Pualam, Andi Ruby Arsy; Bulutoding, Lince; yariati, Namla Elfa; Fadhilatunisa, Della; Talaohu, Sanunggarah (InFestasi, 2024)
The decline in state revenue from taxes was due to the existence of taxpayers who did not comply in carrying out their tax obligations. The Indonesian government's efforts to make taxpayers comply in carrying out their tax obligations include implementing tax sanctions and the Voluntary Disclosure Program. The purpose of this study was to determine the effect of tax sanctions and Voluntary Disclosure Program on the compliance of individual taxpayers registered at KPP Pratama Makassar Utara. The population in this study were all individual taxpayers registered at KPP Pratama Makassar Utara using a sample of 100 samples based on purposive sampling as a sampling technique. Data analysis used multiple linear regression analysis and Moderated Regression Analysis. The results of this study show that tax sanctions and Voluntary Disclosure Program have a positive and significant effect on taxpayer compliance. The results of this study also indicate that knowledge of taxation has not been able to moderate the relationship between tax sanctions and the Voluntary Disclosure Program on taxpayer compliance.